HIV-Envelope–Dependent Cell-Cell Fusion: Quantitative Studies - Leonor Huerta; Nayali López-Balderas; Evelyn Rivera-Toledo; Guadalupe Sandoval; Guillermo Gómez-Icazbalceta; Carlos Villarreal; Edmundo Lamoyi; Carlos Larralde (The Scientific World Journal)
Interaction in vitro between cells infected with human immunodeficiency virus (HIV) and surrounding, uninfected, target cells often leads to cell fusion and the formation of multinucleated cells, called syncytia. The presence in HIV-infected individuals of virus strains able to induce syncytia in cultures of T cells is associated with disease progression and AIDS. Even in the asymptomatic stage of infection, multinucleated cells have been observed in different organs, indicating that fused cells may be generated and remain viable in the tissues of patients. We used lymphocytic cells transfected for the expression of the HIV-envelope (Env) glycoproteins to develop a method for the direct quantification of fusion events by flow cytometry (Huerta et al., 2006, J. Virol. Methods 138, 17–23; López-Balderas et al., 2007, Virus Res. 123, 138–146). The method involves the staining of fusion partners with lipophilic probes and the use of fluorescence resonance energy transfer (FRET) to distinguish between fused and aggregated cells. We have shown that such a flow-cytometry assay is appropriate for the screening of compounds that have the potential to modulate HIV-Env–mediated cell fusion. Even those syncytia that are small or few in numbers can be detected. Quantitative analysis of the fusion products was performed with this technique; the results indicated that the time of reaction and initial proportion of fusion partners determine the number, relative size, and average cellular composition of syncytia. Heterogeneity of syncytia generated by HIV-Env–mediated cell-cell fusion may result in a variety of possible outcomes that, in turn, may influence the biological properties of the syncytia and surrounding cells, as well as replication of virus. Given the myriad immune abnormalities leading to AIDS, the full understanding of the extent, diverse composition, and role of fused cells in the pathogenesis of, and immune response to, HIV infection is an important, pending issue.